دلالة مفهوم الموافقة وأثرها في استنباط الأحكام الشرعية لدى الأصوليين / The meaning of the concept of corresponding meaning (muwafaqah) and its implications in formulating the - (Idris Khuya/ Fatimah Bamati), إدريس بن خويا/أ. فاطمة (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2015)
ملخص البحث: تعدّ الدلالة من أهم القضايا الأساسية في الفكر الأصولي، فمن أساسيات البحث الدلالي في الفكر الأصولي استنباط الأحكام الشرعية من القرآن الكريم والحديث النبوي الشريف، وقد تعددت الدلالات فيها، ومنها: المطلق والمقيد، العام والخاص، والمنطوق الصريح وغير الصريح، والمحكم والمتشابه والمفسر والمحكم، والمفهوم بنوعيه الموافقة والمخالفة. بحثت هذه الدراسة في نوع دلالي واحد لتبيين سبل استنباط الأحكام الشرعية عبر استثمار دلالة مفهوم الموافقة عند الأصوليين، ثمّ تناولت الحديث عن حد مفهوم الموافقة عند اللغويين والأصوليين، وبالبدء بالمفهوم المعجمي ثمّ الاصطلاحي، وبالوقوف على المصادر الأصولية للتعريف به اصطلاحاً، وبعدها وقفت على إشكالية جوهرية ظلت محط خلاف بين الدارسين الأصوليين لمدّة ليست بالقصيرة، والمتمثلة في إشكالية تحديد مفهومه، وتطرقت إليها في حديث مطول، ثمّ وقفت على أنواع المفهوم التي منها الموافقة والمخالفة. فقد خصص الحديث حول مفهوم الموافقة عبر إبراز المصطلحات المتداخلة معه بالتفرقة بينهما، وبعدها الإشارة إلى نوعيه؛ كلحن الخطاب، وفحوى الخطاب. من النتائج التي خرجت بها الدراسة ما يأتي: تعدّ دلالة المفهوم دلالة خارجية تدرك بمعزل عن دلالة المنطوق، وأنّ ما انتهى إليه الشوكاني هو أنّ مفهوم الموافقة دلالة اللفظ على ثبوت حكم المنطوق والمسكوت عنه سواء أكان المسكوت عنه أولى بالحكم من المنطوق به أم كان مساوياً له، ويعتبر المنطوق غير الصريح اللازم الذي لا يذكر في الكلام، بينما هو معنى إن دلّ عليه الكلام في محل النطق، وأنّ المفهوم هو ما دل عليه اللفظ في غير محل النطق، وتعتبر دلالة فحوى الخطاب هي الحكم الذي ينصرف إليه الذهن بالأولوية؛ بينما دلالة لحن الخطاب فهي الحكم المستنبط الذي ينصرف إليه الذهن بالمساواة لدلالة المنطوق؛ أي يكون حكم غير المذكور مساوياً لحكم المذكور. الكلمات المفتاحية: الدلالة– المفهوم- الموافقة– المخالفة- الاستنباط. Abstract: Meaning has always been a central issue in Islamic legal theory. The derivation of sharia’ judgments from the Holy Koran and the prophetic traditions is one of the fundamentals in the issue of meaning in this discipline. Meaning is categorized into these types: absolute or with condition, general or specific, explicitly expressed or implicit, undisputable, similar or interpretable and the concept of corresponding meaning (muwafaqah) and non-corresponding meaning (mukhalafah). This paper aims to discuss only the concept of muwafaqah by the Islamic legal theorists in formulating sharia’ judgements through focusing on the meaning of the concept among the legal theorist as well as its limitation in accordance to the opinions of Arabic language scholars and the Islamic legal theorists. The study highlights its lexical and terminological meaning with reference to the sources of Islamic legal theory. Subsequently, the long standing central issue of the dispute among the scholars of Islamic legal theory is on determining its concept of which the paper will thoroughly examine. Both concepts of corresponding and non-corresponding meaning will be analyzed. Some other terminologies which are seemingly similar to it will be investigated and for the purpose of distinguishing between them. Two types of the concept of muwafaqah will be studied: tone of discourse (lahn al-khitab) and the content of discourse (content of discourse). Among the conclusions of the study: the meaning of the concept is regarded as an external meaning perceivable separately from the verbal meaning. It is also concluded that Syaukani’s understanding of the concept of muwafaqah is the meaning of a word with both certainty in judgement that is expressed verbally and what is perceived silently regardless whether the judgement derived from each of two is more important than the other of similar in priority. The implicit verbal meaning is the inherent meaning that is left unexpressed. But if the saying indicates it in the form of expression then in become significant. The concept is what being indicated by the word at other than the mode of articulation. The meaning from the content of a discourse (fahwa) is the judgement of the notion that is perceivable instantly by the thought in order of priority while the meaning derived from the tone of the discourse (lahn) is the judgement perceived by the thought in similar manner with the verbal meaning in which the unarticulated judgement similar to the articulated judgement. Keywords: meaning –concept– corresponding meaning– non-corresponding meaning– formulation of judgement. Abstrak: Makna adalah satu perbahasan utama dalam bidang Usul Fiqh. Kaedah memutuskan hukum-hakam daripada Alquran dan Hadis adalah satu daripada prinsip-prinsip dalam persoalan makna yang dibahaskan dalam bidang ini. Makna dikategorikan kepada tiga, mutlak atau terikat, am atau khas, terang atau tersirat, sabit, sama atau boleh ditakwil dan seterusnya mafhum muwafaqah(setara) atau mukhalafah(berbeza). Kajian ini bertujuan untuk hanya membincangkan mafhum muwafaqah oleh ulama Usul Fiqh dalam memutuskan hukum hakam. Ini dilakukan dengan melihat maksud konsep tersebut dalam kalangan ulama Usul Fiqh disamping menyorot pendapat para ahli bahasa Arab tentang lapangan makna dan batasannya. Makna perkataan dan instilahnya berdasarkan sumber-sumber Usul Fiqh. Dasar dan aspek yang menjadi perdebatan tentang konsep ini akan turut dikupas. Kedua-dua konsep muwafaqah dan mukhalafah akan turut dikaji. Beberapa istilah-istilah lain yang mirip dengan konsep ini akan dibincangkan untuk dilihat perbezaan-perbezaan di antaranya. Dua kategori mafhum muwafaqah akan dikaji: nada wacana (lahn al-khitab) dan kandungan wacana (fahwa al-khitab). Di antara kesimpulan-kesimpulan kajian ialah: maksud konsep tersebut dianggap sebagai satu maksud yang difahami secara sendiri dan berbeza daripada maksud ujaran verbal. Dalam hal ini, pendapat Shaukani tentang muwafaqah ialah maksud perkataan yang sabit hukumnya yang diujarkan secara verbal dan yang difahami secara tanpa perlu dinyatakan tidak kira samada hukum yang diputuskan berdasarkan daripada salah satu daripada kedua-duanya adalah lebih penting daripada salah satu daripada kedua-duanya atau serupa pentingya. Maksud ujaran verbal tersirat pula ialah maksud yang terkandung pasti yang tidak dinyatakan. Namun jika sekiranya dinyatakan secara verbal, ia menjadi penting. Sesuatu yang difahami itu juga turut merangkumi sesuatu yang turut difahami akal yang bukan sahaja melalui pernyataan verbal. Maksud daripada kandungan sesuatu wacana itu pula ialah hukum yang difahami secara terus secara mengikut tingkat kepentingannya manakala maksud yang disimpulkan daripada nada sesuatu ungkapan itu ialah maksud yang sama dapat difahami secara verbal yang menjadikan hukum yang diputuskan melaluinya adalah sama dengan hukum yang diputuskan secara bukan verbal. Kata kunci: Maksud - konsep – mafhum muwafaqah – mafhum mukhalafah – formulasi hukum